Diagnostic evaluation of people with hypertension in low income country: cohort study of "essential" method of risk stratification. (19th September 2008) - Montalvo, Gregorio; Avanzini, Fausto; Anselmi, Mariella; Prandi, Rosanna; Ibarra, Samuel; Marquez, Monica; Armani, Daniela; Moreira, Juan-Martín; Caicedo, Cynthia; Roncaglioni, Maria Carla; Colombo, Fabio; Camisasca, Paola; et al.
Abstract : Objectives To explore the predictive power of a risk stratification method for people with hypertension based on "essential" procedures (that is, available in economically less developed areas of the world), comparing it in the same population with the results given by the method suggested by the 1999 World Health Organization-International Society of Hypertension (WHO-ISH) guidelines. Design Prospective cohort study of outcomes according to cardiovascular risk profile at baseline. Setting Primary care in a poor rural area of the Ecuadorian forest. Participants 504 people with hypertension prospectively monitored for a mean of 6.7 (SD 2.3) years. Interventions Essential data included blood pressure, medical history, smoking, age, sex, and diagnosis of diabetes; the WHO-ISH methods additionally included measurement of fasting blood glucose, total cholesterol, and creatinine, urinalysis, and electrocardiography. Main outcome measures Cardiovascular events and total deaths. Results With both methods there was a highly significant association between the level of predicted risk and the incidence of cardiovascular events and of total deaths: up to three quarters of all cardiovascular events and two thirds of all deaths were reported among people classified as at high or very high risk with either method. The predictive discrimination of the essential method is comparable with the WHO-ISH with C statistics (95% confidence interval) of 0.788 (0.721 to 0.855) and 0.744 (0.673 to 0.815), respectively, for cardiovascular events and 0.747 (0.678 to 0.816) and 0.705 (0.632 to 0.778) for total mortality. Conclusions The risk stratification of patients with hypertension with an essential package of variables (that is, available and practicable even in the economically less developed areas of the world) serves at least as well as the more comprehensive method proposed by WHO-ISH.